2010
DOI: 10.1002/asna.201011353
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur abundances in halo stars from multiplet 3 at 1045 nm

Abstract: Sulphur is a volatile α-element which is not locked into dust grains in the interstellar medium (ISM). Hence, its abundance does not need to be corrected for dust depletion when comparing the ISM to the stellar atmospheres. The abundance of sulphur in the photosphere of metal-poor stars is a matter of debate: according to some authors, [S/Fe] versus [Fe/H] forms a plateau at low metallicity, while, according to other studies, there is a large scatter or perhaps a bimodal distribution. In metal-poor stars sulph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 23 publications
4
28
1
Order By: Relevance
“…2. In contrast to previous studies by Israelian & Rebolo (2001), Takada-Hidai et al (2002), Caffau et al (2005Caffau et al ( , 2010, no stars with extremely high sulphur abundances are observed, nor are the sulphur abundances found to increase towards lower metallicities. In fact, the opposite is observed -a linear fit for the metal-poor ( is found to decrease as the metallicity increases, which is expected of α-elements (solid line).…”
Section: Sulphur Abundancescontrasting
confidence: 99%
See 1 more Smart Citation
“…2. In contrast to previous studies by Israelian & Rebolo (2001), Takada-Hidai et al (2002), Caffau et al (2005Caffau et al ( , 2010, no stars with extremely high sulphur abundances are observed, nor are the sulphur abundances found to increase towards lower metallicities. In fact, the opposite is observed -a linear fit for the metal-poor ( is found to decrease as the metallicity increases, which is expected of α-elements (solid line).…”
Section: Sulphur Abundancescontrasting
confidence: 99%
“…On the other hand, a number of studies (e.g, Ryde & Lambert 2004;Korn & Ryde 2005;Nissen et al 2007;Spite et al 2011) have found little to no evidence of high ([S/Fe] 0.6) sulphur abundances at any metallicity and instead argued that sulphur is a fairly typical α-element and forms a plateau of [S/Fe] ∼ 0.3 below [Fe/H] ∼ −1, which points to an origin in Type II supernovae (e.g., Kobayashi et al 2006). Finally, a combination of the two patterns, which implies a very complex history of chemical evolution of sulphur, has been found by Caffau et al (2005Caffau et al ( , 2010. It is open to debate whether there exist metal-poor stars with extremely high sulphur abundances, and the discrepant findings of previous studies could either reflect reality or differences in the employed analyses.…”
Section: Introductionmentioning
confidence: 96%
“…These studies are also consistent with a plateu of enhanced [S/Fe] values at low metallicities, both in the Galactic halo (Caffau et al 2010;Jönsson et al 2011;Takeda & Takada-Hidai 2012) and also in globular clusters (Kacharov et al 2015).…”
Section: Based On Observations Made With Eso/vlt/flames At the La Silsupporting
confidence: 88%
“…The S-poor Spite et al (2011;dark grey). Sulphur abundances in halo stars determined from multiplet 3 are shown with pluses (Takeda & Takada-Hidai 2012), asterisks (Jönsson et al 2011), and exes (Caffau et al 2010). In all cases, NLTE corrections have been applied.…”
Section: Resultsmentioning
confidence: 99%
“…By extrapolating the NLTE results from the grid of Takeda et al (2005) to the stellar parameters of our stars, we found According to calculations by Jönsson et al (2011), based on the 3D model atmospheres of Collet et al (2007Collet et al ( , 2009, the 3D corrections for S abundances derived from multiplet 3 are constant and positive at all metallicities for stars with similar parameters to ours and are in the order of Δ 3D = +0.20 dex. Caffau et al ( , 2010 explored the 3D effects of multiplet 3 in dwarf stars and also found positive corrections based on the CO 5 BOLD 3D model atmospheres. Although it is inconsistent to apply their results to giant stars, there is an agreement that the 3D corrections for the lines at 1045 nm are always positive.…”
Section: Nlte and 3d Effectsmentioning
confidence: 99%